ANALISIS PAJAK PENGHASILAN BADAN TERUTANG PADA PT. XXX TAHUN 2018 - Nikomang Kandy Sani, Purnamawati Helen Widjaya (Jurnal Paradigma Akuntansi, 2020)
The purpose of this research is to determine whether PT. XXX has made a fiscal reconciliation based on the current taxation laws. Researchers also tested whether PT. XXX has calculated the Unpaid Corporate Income Tax based on the current taxation laws and made a comparison between the calculation of the Unpaid Corporate Income Tax before analysis with the calculation of the Unpaid Corporate Income Tax after analysis. The financial statements used in this study are the financial statements of PT. XXX 2018.